The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1590/s0101-81752006000400003
|View full text |Cite
|
Sign up to set email alerts
|

Redescription of the advertisement call of Aplastodiscus arildae (Cruz & Peixoto) and description of the call of Aplastodiscus weygoldti (Cruz & Peixoto) with general notes about the genus in Southeastern Brazil (Anura, Hylidae)

Abstract: The study of anuran advertisement calls is very significant for it is an important premating premating mechanism. Herein we redescribe the advertisement call of Aplastodiscus arildae from an area near type-locality and describe the advertisement call of A. weygoldti comparing them to previously described advertisement calls of species of the genus Aplastodiscus. Both advertisement calls are simple, non-modulated calls, very similar to each other, but significantly different in what matters to call duration. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
(16 reference statements)
0
7
1
1
Order By: Relevance
“…(Cochran, 1955;Lutz, 1973;; among others). Some authors suggested a red-orange iris as a possible synapomorphy of the group (Carvalho-e-Silva and Carvalho-e-Silva, 2005;Orrico et al, 2006). However, we find that iris color varies among individuals of the same population; at the type locality of A. arildae, we recorded two individuals with coppercolored irises, whereas all other individuals had red irises.…”
Section: The Position Of a Sibilatuscontrasting
confidence: 64%
See 4 more Smart Citations
“…(Cochran, 1955;Lutz, 1973;; among others). Some authors suggested a red-orange iris as a possible synapomorphy of the group (Carvalho-e-Silva and Carvalho-e-Silva, 2005;Orrico et al, 2006). However, we find that iris color varies among individuals of the same population; at the type locality of A. arildae, we recorded two individuals with coppercolored irises, whereas all other individuals had red irises.…”
Section: The Position Of a Sibilatuscontrasting
confidence: 64%
“…Apparently, both species occur at this locality (Silva-Soares et al, 2011;Silva et al, 2012). Orrico et al (2006) described the call of A.…”
Section: The Position Of a Sibilatusmentioning
confidence: 99%
See 3 more Smart Citations